Animal welfare in the humanities and natural sciences - El-Jai, Julita (Studia Ecologiae et Bioethicae, 2008)
In this article I will focus on animal welfare as an example of interdisciplinary (philosophy - food ethics and natural science) issue. Decisions about animal welfare have a scientific, political and ethical meaning. We can notice the increasing animal welfare standards in EU. Consumers in developed countries are concerned about the welfare of animals and demand the appropriate, healthy and safe food, which protects the environment. EU protocol obliging member states to pay full regard to animal welfare in forming relevant policy and legislation.